PENGARUH KUALITAS PELAYANAN ADMINISTRASI, SARANA PRASARANA, DAN PERILAKU PEGAWAI TERHADAP KEPUASAN MASYARAKAT PEMOHON E-KTP DAN AKTE KELAHIRAN PADA DINAS KEPENDUDUKAN DAN CACATAN SIPIL KABUPATEN BIREUEN - Konadi, Win; Syahniar (LPPM-UNIKI, 2021)
This study aims to assess and measure the magnitude; 1) The effect of the service system on the community satisfaction of e-KTP-e applicants and birth certificates, 2) the influence of infrastructure on the community satisfaction of e-KTP-e applicants and birth certificates, 3) the effect of service employee behavior on community satisfaction with e-KTP and the applicant for a birth certificate, and 4) the influence of the service system, facilities, and employee behavior on the community satisfaction of applicants for KTP-el and birth certificates at the Civil Service Population and Civil Disability Service. Bireuen District. With the research object is the people of Bireuen Regency who submitted and made El-KTP and birth certificates as many as 70 samples. With a path analysis approach. The results showed that; A). There is a direct and indirect effect of service quality factors on the satisfaction of the community managing and making KTP-e and child birth certificates by 33.58%. b). The magnitude of the influence of service facilities and infrastructure factors on the satisfaction of the people who care for and make e-KTPs and birth certificates for children is 16.13%, c). And the influence of employee behavior factors on community satisfaction who care for and make e-KTPs and birth certificates for children at the Population and Civil Registry Office of Bireuen Regency is 20.89%. Based on the size of the determination coefficient of 0.705, it explains that the contribution of the aspects of service quality, service facilities and infrastructure and employee behavior to community satisfaction at the Population and Civil Registry Office of Bireuen Regency is 70.5%. Meanwhile, the remaining role of the variable that was not examined was 29.5%, indicating that there are other factors that can influence the variable of community satisfaction